Study of Salty Taste Sensor Based Graphite PVC Electrode Modified with Polypyrrole-Carbon Black (PPy-CB) - Diah Ayu Suci Kinasih (Department of Physics Universitas Gadjah Mada, 2025)
A successful salty taste sensor was developed using solid-contact electrodes with graphite PVC composite substrates. The fabricated sensor was characterized using cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS). The characterization results showed the addition of polypyrrole-carbon black (PPy-CB) material increased the capacitance, conductivity, and enlarged the graphite PVC electrode surface area. The selectivity of the sensor was measured on an electrode that has been coated with a lipid membrane mixture of tetradodecyl ammonium bromide (TDDAB) and 1-hexadecanol against basic taste samples using the impedimetric method and processed with PCA analysis. The result showed good salty taste selectivity with a silhouette coefficient value of 0.90. The constructed sensor demonstrated linear behavior towards standard salty substances (NaCl) with a sensitivity of -4.36 kΩ/decade and R2 = 0.99 in the sensing range of 0.1 to 30 mM. The study's findings suggest that graphite PVC electrodes modified with PPy-CB and lipid membrane combined with the impedimetric measurement method exhibit good selectivity and sensitivity in detecting salty taste.